Physiological and proteomic insights into melatonin-mediated delay in postharvest quality deterioration of blue honeysuckle fruit - Ruiling Liu; Lun Tao; Xiangjun Fang; Chaoyi Shen; Junwei Huo; Maratab Ali; Huizhi Chen; Hailong Yang; Haiyan Gao (Postharvest Biology and Technology, 2026)

Selective iron removal from Fe-PGMs alloys for platinum group metals concentration: Dissolution behavior of PGMs and ultrasound-assisted leaching - Han Yang; Yong Li; Xilong Wu; Ruiling Yuan; Chao Wang; Shengnan Lin; Jibiao Han; Kuo Liu (Journal of Environmental Chemical Engineering, 2026)

1-Methylcyclopropene-mediated organic acid and sugar homeostasis enhances postharvest quality and shelf-life of fresh goji berry - Maratab Ali; Huizhi Chen; Weijie Wu; Ben Niu; Xiangjun Fang; Chaoyi Shen; Guannan Wang; Hangjun Chen; Ting Huang; Ming Yin; Ruiling Liu; Haiyan Gao (Food Chemistry, 2026)

Quantitative proteomics reveals energy metabolism remodeling in Bacillus cereus spores under pulsed light treatment - Ruiling Lv; Jiawei Liu; Qin Li; Yajin Qi; Jianwei Zhou; Shao Chen (Food Research International, 2026)

Preparation and application of a sustained and unidirectional release active gelatin-sodium alginate/zein Janus film - Ben Niu; Yineng Liu; Ruiling Liu; Xiangjun Fang; Weijie Wu; Hangjun Chen; Chuan Tong; Huizhi Chen; Haiyan Gao (Food Hydrocolloids, 2026)

Comparative effects of liquid nitrogen rapid freezing, micro-freezing liquid-assisted freezing, and conventional freezing on the physicochemical properties, moisture distribution, microstructure, and protein characteristics of beef steaks - Ling Jiang; Donghong Liu; Wenjun Wang; Ruiling Lv; Songfeng Yu; Yunli Deng; Jianwei Zhou (Food Control, 2026)

A dual-dynamic-bond network enabled, ultra-stretchable, and self-healing hydrogel for fresh produce damage prevention in postharvest logistics - Guannan Wang; Mengqi Zheng; Huizhi Chen; Ruiling Liu; Weijie Wu; Xiangjun Fang; Chaoyi Shen; Hangjun Chen; Haiyan Gao (Chemical Engineering Journal, 2026)

Inactivating Bacillus cereus spores with pulsed light: roles of thermal and reactive oxygen species-mediated mechanisms - Qin Li; Jiawei Liu; Jianwei Zhou; Donghong Liu; Yajin Qi; Ruiling Lv (Food Research International, 2026)

Investigation of the Degradation Mechanism of Dibutyl Phthalate in Soil Using Alkali-Modified Biochar and Persulfate Systems - Ruiling Zhang; Xinyu Zhang; Shuang Du; RuiRui Zhang; Jiayong Gao; Youjun Zhang; Jinpeng Liu (Water, Air, & Soil Pollution, 2026)

Coupled water-vapor-heat-salt transport mechanisms in sulfate saline soils under the pot cover effect: numerical simulation and experimental validation - Ruiling Zhang; Yaling Chou; Mingli Zhang; Fengxi Zhou; Hongbo Liu (Journal of Mountain Science, 2026)

Effect of liquid-medium properties on ultrasound inactivation efficiency and mechanism against Escherichia coli and Listeria monocytogenes - Bin Yang; Tingting Chen; Ruyu Zhang; Haiqi Chen; Wenjun Wang; Ruiling Lv; Donghong Liu (Food Bioscience, 2026)

Biochar enhances rice rhizodeposited carbon stabilization through distinct pathways of iron association and aggregate occlusion in two contrasting paddy soils - Ruiling Ma; Yujia Yu; Ruiyu Wang; Zheng Zhao; Zuhang Shen; Qi Yi; Shaopan Xia; Rongjun Bian; Xuhui Zhang; Zhiwei Liu; Kun Cheng; Jufeng Zheng (Biology and Fertility of Soils, 2026)

Slightly acidic electrolyzed water enhances fruit disease resistance in longans by activating phenylpropanoid and flavonoid pathways - Qingqing Liu; Shengtai Lin; Yuxin Wu; Zhongqi Fan; Ruiling Zhuo; Yifen Lin; Boqiang Li; Shiping Tian; Mengshi Lin; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2026)

Unraveling the spatial chemical heterogeneity of Lentinula edodes: Integrative metabolomics and machine learning for cultivar and origin classification - Shenglong Lu; Chaoyi Shen; Ben Niu; Ruiling Liu; Huizhi Chen; Hangjun Chen; Xiangjun Fang; Lishu Wang; Ming Yin; Weijie Wu; Haiyan Gao (Food Chemistry, 2026)

Application of ε-poly-L-lysine alleviates postharvest disease in fresh longans incurred by Phomopsis longanae Chi via regulating the metabolisms of reactive oxygen species and membrane lipids - Xiaoze Dai; Qingqing Liu; Junzheng Sun; Ruiling Zhuo; Yifen Lin; Mengshi Lin; Boqiang Li; Shiping Tian; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2026)

Separation and enrichment of platinum from spent petroleum reforming catalysts via carrier-directed dissolution under alkaline conditions - Qingfeng Xiong; Han Yang; Lang Liu; Jibiao Han; Yu Shen; Wenhui Ma; Yakun Zhang; Ruiling Yuan; Chao Wang (Journal of Environmental Chemical Engineering, 2026)

Study on the horizontal dynamic characteristics of cement-soil composite pipe Piles: Field test and finite element analysis - Ruiling Zhang; Hongbo Liu; Guoliang Dai (Soil Dynamics and Earthquake Engineering, 2026)

State-of-the-art insights into hydrogel innovations from structural engineering to smart preservation: Research trends and future directions - Yan Xu; Yiyi Cheng; Tao Yang; Huizhi Chen; Ben Niu; Xiangjun Fang; Weijie Wu; Chaoyi Shen; Guannan Wang; Bangdi Liu; Ruiling Liu; Haiyan Gao (Trends in Food Science & Technology, 2026)

Dynamic changes in epidermal wax composition and quality of three goji berry varieties during postharvest storage - Ben Niu; Zihao Zong; Yifan Ding; Huizhi Chen; Weijie Wu; Maratab Ali; Mohamed A. Farag; Xiangjun Fang; Ting Huang; Chaoyi Shen; Li-shu Wang; Ruiling Liu; et al. (Postharvest Biology and Technology, 2026)

Decolorization of malachite green by free and immobilized Pseudomonas sp. strain C2-4 - Yue Xiao; Yichao Zhao; Yurong Yan; Jinyan Liu; Ruiling Lyu; Yongliang Zheng; Xia Fan (World Journal of Microbiology and Biotechnology, 2026)

Ultraviolet-C treatment regulates the greening process of water bamboo (Zizania latifolia) shoots during postharvest storage - Xuening Zhao; Ruiling Liu; Yanchao Han; Ben Niu; Huizhi Chen; Xiangjun Fang; Haiyan Gao; Hangjun Chen (Postharvest Biology and Technology, 2025)

The role of silica in biomass for calcium-modified biochar: Phosphorus removal mechanism and potential as a phosphate fertilizer application - Yongyi Chen; Ruiling Zhang; Jiayong Gao; Mujun Han; Songyan Qin; Kai Liu; Yajie Shu; Ruirui Zhang; Chang Shi; Yue Zheng (Journal of Environmental Sciences, 2025)

Efficacy and antibacterial mechanism of intense pulsed light against Escherichia coli: Photochemical and physical effect - Zihan Ye; Tingting Chen; Ruyu Zhang; Ruiling Lv; Songfeng Yu; Jianwei Zhou; Wenjun Wang; Donghong Liu (Food Bioscience, 2025)

Hypothermal effects of cold anesthesia on the vitality and muscle quality of live Chinese mitten crab (Eriocheir sinensis) - Laixin Chen; Yanchao Han; Honglei Mu; Ben Niu; Ruiling Liu; Guannan Wang; Huizhi Chen; Lishu Wang; Hangjun Chen; Haiyan Gao (Food Research International, 2025)

Utilizing air discharge to preserve post-harvest quality of lotus root by suppressing fusarium oxysporum - Pengyue Zhang; Huizhi Chen; Ben Niu; Honglei Mu; Ruiling Liu; Yanchao Han; Ming Yin; Chaoyi Shen; Haiyan Gao; Hangjun Chen (Food Chemistry, 2025)

Ultrasound-enhanced inactivation of Escherichia coli O157: H7 from wastewater in the citric acid-assisted nano zerovalent iron heterogeneous Fenton system: Effectiveness and mechanisms - Ting-Ting Chen; Wenjun Wang; Ruiling Lv; Donghong Liu (Journal of Water Process Engineering, 2025)

γ-Aminobutyric acid: An emerging biomolecule for maintaining the postharvest quality of fresh fruits and vegetables: A meta-analysis - Maratab Ali; Ben Niu; Weijie Wu; Akhtar Ali; Huizhi Chen; Ming Yin; Chaoyi Shen; Ruiling Liu; Haiyan Gao (Food Chemistry, 2025)

Pot-cover effect in permafrost embankment: Laboratory experimental reproduction and prevention measures simulation - Yuefeng Liu; Mingli Zhang; Dongmiao Hao; Zhi Wen; Ruiling Zhang; Wei Feng (Cold Regions Science and Technology, 2025)

Salicylic acid nanoliposomes treatment alleviates chilling injury in postharvest baby ginger by regulating membrane lipid metabolism - Zhenzhen Mi; Honglei Mu; Yanchao Han; Ruiling Liu; Ben Niu; Guannan Wang; Huizhi Chen; Haiyan Gao; Hangjun Chen (Food Chemistry, 2025)

Silk protein functionalized coatings and films as a novel biomaterial for fruit and vegetable preservation: current state and future prospects - Yan Wang; Weijie Wu; Ruiling Liu; Huizhi Chen; Haiyan Gao (Current Opinion in Food Science, 2025)

The divergent response of fungal and bacterial necromass carbon in soil aggregates under biochar amendment in paddy soil - Mengtao Zhu; Zhiwei Liu; Qi Yi; Ruiling Ma; Man Xu; Kaiyue Song; Rongjun Bian; Jufeng Zheng; Xuhui Zhang (Plant and Soil, 2025)

Effects of negative air ion treatment on postharvest storage quality and anthocyanin metabolism of grape - Chan Ma; Yanchao Han; Ruiling Liu; Ben Niu; Chaoyi Shen; Huizhi Chen; Ming Yin; Weijie Wu; Haiyan Gao (Food Chemistry, 2025)

The transcription factor CeWRI3 functions in TAG accumulation through activating CeOLE2 in Cyperus esculentus - Zhi Zou; Xiaowen Fu; Na Li; Panyan Zheng; Ruiling Wang; Hongyan Liu; Jiaquan Huang; Yongguo Zhao (Plant Cell Reports, 2025)

Development of cushioning-antibacterial dual-functional cellulose packaging and its application for the Chinese bayberry during simulated transportation vibration - Yifan Xue; Ben Niu; Yanchao Han; Weijie Wu; Guannan Wang; Ming Yin; Xiangjun Fang; Ruiling Liu; Hangjun Chen; Haiyan Gao; Honglei Mu (Food Packaging and Shelf Life, 2025)

The anti-Alzheimer's disease effects of ganoderic acid A by inhibiting ferroptosis-lipid peroxidation via activation of the NRF2/SLC7A11/GPX4 signaling pathway - Qingyang Lu; Nan Shao; Ziyi Fang; Zhaorong Ouyang; Yiran Shen; Ruiling Yang; Houli Liu; Biao Cai; Tao Wei (Chemico-Biological Interactions, 2025)

Advancements and perspectives of antimicrobial effects of combination mode nonthermal strategies - A review - Ruyu Zhang; Yong Deng; Ruiling Lv; Wenjun Wang; Donghong Liu (Food Bioscience, 2025)

Advancements and perspectives of novel freezing and thawing technologies effects on meat: A review - Ling Jiang; Donghong Liu; Wenjun Wang; Ruiling Lv; Songfeng Yu; Jianwei Zhou (Food Research International, 2025)

Composition and micromorphological determination of blue honeysuckle fruit (Lonicera caerulea L.) cuticular wax and its effects on fruit post-harvest quality - Ze Peng; Huizhi Chen; Ben Niu; Weijie Wu; Hangjun Chen; Mohamed A. Farag; Yifan Ding; Ruiling Liu; Haiyan Gao (Food Chemistry, 2025)

Shiitake mushroom-derived extracellular nanovesicles: Preparation, characterization, and inhibition of Caco-2 cells - Xueli Yang; Zihao Zong; Ben Niu; Hangjun Chen; Weijie Wu; Xiangjun Fang; Ruiling Liu; Haiyan Gao; Honglei Mu (Food Chemistry, 2025)

Silk protein: A novel antifungal and edible coating for strawberry preservation - Yan Wang; Weijie Wu; Ruiling Liu; Ben Niu; Xiangjun Fang; Hangjun Chen; Mohamed A. Farag; Li-Shu Wang; Guannan Wang; Hailong Yang; Huizhi Chen; Haiyan Gao (Food Chemistry, 2025)

High UV-shielding polyvinyl alcohol/chitosan-based transparent bioplastic film for food preservation - Mei Bao; Honglei Mu; Ben Niu; Ruiling Liu; Huizhi Chen; Hangjun Chen; Lishu Wang; Yanchao Han; Guannan Wang; Haiyan Gao (Food Packaging and Shelf Life, 2025)

Occurrence, bioaccumulation, and partitioning of phthalate acid esters in the third largest freshwater lake (Lake Taihu) in China - Ruiling Liu; Yuqiang Tao (Environmental Research, 2024)

Half-antibody spur one-to-one recognition mechanism can function with chemical-staining technology for next-generation lateral flow immunoassay - Jingke Xu; Jing Zhou; Kai Liu; Tong Bu; Leina Dou; Rui Shu; Sijie Liu; Shaochi Wang; Xuechi Yin; Daohong Zhang; Ruiling Zhang; Jie Cheng; et al. (Chemical Engineering Journal, 2024)

Exogenous microbubbles contribute to valorization of microalgal compounds by ultrasound-assisted extraction - Yong Deng; Lihua Fan; Wenjun Wang; Ruiling Lv; Donghong Liu (Bioresource Technology, 2024)

Nitrogen removal pathways and microbial community structure in the aerobic granular sludge reactor with co-existence of granules and flocs - Yunlong Zheng; Ruiling Bao; Yan Liu; Wei Cheng; Changyong Wu; Lianqing Xue; Qing Liu (Process Safety and Environmental Protection, 2024)

Identification of extracted antioxidants from Citrus aurantium 'Changshanhuyou' residue against digestive enzyme activities and airway smooth muscle cells proliferation using UPLC-MS/MS - Xinyue Zhou; Junyang Wang; Han Wang; Peng Lu; Qiong Huang; Ming Huang; Ruiling Lv; Donghong Liu; Wenjun Wang (Food Bioscience, 2024)

Examining starch metabolism in lotus roots (Nelumbo nucifera Gaertn.) during post-harvest storage at different temperatures - Xinxin Gong; Ruiling Liu; Yanchao Han; Ben Niu; Weijie Wu; Huizhi Chen; Xiangjun Fang; Honglei Mu; Haiyan Gao; Hangjun Chen (Food Chemistry, 2024)

Recent advances in Zizania latifolia : A comprehensive review on phytochemical, health benefits and applications that maximize its value - Weijie Wu; Yanchao Han; Ben Niu; Baiqi Yang; Ruiling Liu; Xiangjun Fang; Huizhi Chen; Shangyue Xiao; Mohamed A. Farag; Shiqi Zheng; Jianbo Xiao; Hangjun Chen; et al. (Critical Reviews in Food Science and Nutrition, 2024)

A novel function of benzoic acid to enhance intestinal barrier defense against PEDV infection in Piglets - Ruiling Liu; Rongfeng Tang; Yuchen Li; Qiu Zhong; Yunlei Cao; Qian Yang (Veterinary Microbiology, 2024)

The dual function of calcium ion in fruit edible coating: Regulating polymer internal crosslinking state and improving fruit postharvest quality - Yiqin Zhang; Qi Kong; Ben Niu; Ruiling Liu; Huizhi Chen; Shangyue Xiao; Weijie Wu; Wanli Zhang; Haiyan Gao (Food Chemistry, 2024)

Simulated gastrointestinal digestion of walnut protein yields anti-inflammatory peptides - Wei Xia; Yuan Gao; Xiangjun Fang; Long Jin; Ruiling Liu; Li-Shu Wang; Yangyong Deng; Junlong Gao; Hailong Yang; Weijie Wu; Haiyan Gao (Food Chemistry, 2024)

VcMYB30 enhances wax production and maintains fruit quality by regulating cuticular wax biosynthesis genes - Qi Kong; Ruiling Liu; Weijie Wu; Huizhi Chen; Yanchao Han; Xiangjun Fang; Yiqin Zhang; Hangjun Chen; Honglei Mu; Haiyan Gao; Jianye Chen (Postharvest Biology and Technology, 2024)

Evaluation of multiscale mechanisms of ultrasound-assisted extraction from porous plant materials: Experiment and modeling on this intensified process - Jiaheng Li; Wenjun Wang; Weidong Xu; Yong Deng; Ruiling Lv; Jianwei Zhou; Donghong Liu (Food Research International, 2024)

Biomimetic hybrid porous microspheres with plant membrane-wall structure for evaluating multiscale mechanisms of ultrasound-assisted mass transfer - Jiaheng Li; Wenjun Wang; Weidong Xu; Songfeng Yu; Ruiling Lv; Jianwei Zhou; Donghong Liu (Chemical Engineering Journal, 2024)

3D Models of Sarcomas: The Next-generation Tool for Personalized Medicine - Ruiling Xu; Ruiqi Chen; Chao Tu; Xiaofeng Gong; Zhongyue Liu; Lin Mei; Xiaolei Ren; Zhihong Li (Phenomics, 2024)

Inhibitory effect and action mechanism of perillaldehyde on the Fusarium graminearum in postharvest fresh ginger - Xiuling Meng; Weijie Wu; Ben Niu; Ruiling Liu; Huizhi Chen; Haiyan Gao; Hangjun Chen (Postharvest Biology and Technology, 2024)

miR-306-5p is involved in chitin metabolism in Aedes albopictus pupae via linc8338-miR-306-5p-XM_019678125.2 axis - Ruiling Zhang; Wenjuan Liu; Zhong Zhang (Pesticide Biochemistry and Physiology, 2024)

Importance sampling-based probabilistic performance modeling of low-, mid- and high-strength pipelines under coupling effect of hydrogen-induced damage and corrosion - Yihuan Wang; Zhenwei Zhang; Siming Liu; Ailin Xia; Ruiling Li; Guojin Qin (Process Safety and Environmental Protection, 2023)

Development of bio-based PLA/cellulose antibacterial packaging and its application for the storage of shiitake mushroom - Weitao Wang; Ben Niu; Ruiling Liu; Hangjun Chen; Xiangjun Fang; Weijie Wu; Guannan Wang; Haiyan Gao; Honglei Mu (Food Chemistry, 2023)

Critical taste substances and regulatory pathways of fresh lotus seed pulps at different ripeness stages - Yinai Yang; Ruiling Liu; Yanchao Han; Weijie Wu; Xiangjun Fang; Honglei Mu; Haiyan Gao; Hangjun Chen (Postharvest Biology and Technology, 2023)

Melatonin treatment delays the softening of blueberry fruit by modulating cuticular wax metabolism and reducing cell wall degradation - Ruiling Liu; Shang Fanzhen; Ben Niu; Weijie Wu; Yanchao Han; Hangjun Chen; Haiyan Gao (Food Research International, 2023)

Effect of oxyresveratrol on the quality and membrane lipid metabolism of shiitake mushroom (Lentinus edodes) during storage - Ben Niu; Yingchang Fei; Ruiling Liu; Hangjun Chen; Xiangjun Fang; Weijie Wu; Honglei Mu; Haiyan Gao (Food Chemistry, 2023)

Effect of influent ammonia nitrogen concentration on the phosphorus removal process in the aerobic granular sludge reactor - Wei Cheng; Cong Ma; Ruiling Bao; Xiaoli Yang; Xuankai Zhou; Yan Liu; Qing Liu; Aidong Ruan; Xiang Li (Journal of Environmental Chemical Engineering, 2023)

Facile surface pseudohalide pretreatment of quantum dots for efficient photovoltaics - Zhe Sun; Qinggang Hou; Ruiling Zhang; Jiaxuan Cheng; Jiahua Kong; Keke Wang; Feng Liu; Zhonglin Du; Jianguo Tang (Chemical Engineering Journal, 2023)

Cation engineering in low-dimensional organic-inorganic copper halides for high color rendering index WLEDs - Hong Yin; Wenzhi Li; Zhongyi Wang; Pengyuan Wang; Xin Xu; Peigeng Han; Xin Mao; Feng Liu; Keli Han; Junsheng Chen; Ruiling Zhang (Chemical Engineering Journal, 2023)

Ursolic acid, the main component of blueberry cuticular wax, inhibits Botrytis cinerea growth by damaging cell membrane integrity - Ruiling Liu; Liping Zhang; Shangyue Xiao; Hangjun Chen; Yanchao Han; Ben Niu; Weijie Wu; Haiyan Gao (Food Chemistry, 2023)

Combined effects of NaOH, NaCl, and heat on the characteristics of ovalbumin gel and the exploration of the mechanism of transparent gel formation - Hui Xue; Tianfeng Han; Guowen Zhang; Xiaobo Hu; Ruiling Li; Huilan Liu; Rui Li; Yonggang Tu; Yan Zhao (Food Hydrocolloids, 2023)

Advances of stable isotope technology in food safety analysis and nutrient metabolism research - Wei Xia; Xiangjun Fang; Yuan Gao; Weijie Wu; Yanchao Han; Ruiling Liu; Hailong Yang; Hangjun Chen; Haiyan Gao (Food Chemistry, 2023)

Regulating cobalt chemical state by CeO2 facets preferred exposure for improved ethanol steam reforming - Ruiling Li; Chengyuan Liu; Li Li; Junjie Xu; Jinjin Ma; Jiaqi Ni; Jing Yan; Jun Han; Yang Pan; Yi Liu; Lilin Lu (Fuel, 2023)

In vitro fermentation characteristics of the dietary fiber in bamboo (Phyllostachys edulis) shoots and its regulatory effects on the intestinal microbiota and metabolites - Weijie Wu; Qi Li; Hangjun Chen; Xiangjun Fang; Ben Niu; Ruiling Liu; Honglei Mu; Haiyan Gao (Food Chemistry, 2023)

Application of melatonin delays lignification in postharvest water bamboo shoots in association with energy metabolism - Baiqi Yang; Yanchao Han; Haiyan Gao; Ruiling Liu; Feng Xu; Ruihai Liu; Shangyue Xiao; Bin Li; Hangjun Chen (Postharvest Biology and Technology, 2023)

Aquatic environmental fates and risks of benzotriazoles, benzothiazoles, and p-phenylenediamines in a catchment providing water to a megacity of China - Ruiling Zhang; Shizhen Zhao; Xin Liu; Lele Tian; Yangzhi Mo; Xin Yi; Shiyang Liu; Jiaqi Liu; Jun Li; Gan Zhang (Environmental Research, 2023)

Complete genome sequence of Edgeworthia chrysantha mosaic-associated virus, a tentative new member of the genus Coguvirus (family Phenuiviridae) - Xiaoru Wang; Ruiling Liao; Xinying Yang; Qiyan Liu; Song Zhang; Mengji Cao (Archives of Virology, 2022)

The Mechanism of Stem Cell Aging - Liangyu Mi; Junping Hu; Na Li; Jinfang Gao; Rongxiu Huo; Xinyue Peng; Na Zhang; Ying Liu; Hanxi Zhao; Ruiling Liu; Liyun Zhang; Ke Xu (Stem Cell Reviews and Reports, 2022)
Stem cells have self-renewal ability and multi-directional differentiation potential. They have tissue repair capabilities and are essential for maintaining the tissue homeostasis. The depletion of stem cells is closely related to the occurrence of body aging and aging-related diseases. Therefore, revealing the molecular mechanisms of stem cell aging will set new directions for the therapeutic application of stem cells, the study of aging mechanisms, and the prevention and treatment of aging-related diseases. This review comprehensively describes the molecular mechanisms related to stem cell aging and provides the basis for further investigations aimed at developing new anti-stem cell aging strategies and promoting the clinical application of stem cells.

Efficacy and safety of aripiprazole once-monthly versus oral aripiprazole in Chinese patients with acute schizophrenia: a multicenter, randomized, double-blind, non-inferiority study - Le Xiao; Qian Zhao; An-ning Li; Jushui Sun; Bin Wu; Lina Wang; Honggeng Zhang; Ruiling Zhang; Keqing Li; Xiaojin Xu; Tiebang Liu; Wenshun Zhang; et al. (Psychopharmacology, 2022)

Region-dependent regulation of acute ethanol on γ oscillation in the rat hippocampal slices - Zhihua Liu; Feng Ren; Bin Yang; Hongxing Zhang; Fangli Guo; Xiangyang Zhang; Chengbiao Lu; Ruiling Zhang (Psychopharmacology, 2020)

Correction to: Identification of β‑carboline and canthinone alkaloids as anti‑inflammatory agents but with different inhibitory profile on the expression of iNOS and COX‑2 in lipopolysaccharide‑activated RAW 264.7 macrophages - Pan Liu; Huixiang Li; Ruiling Luan; Guiyan Huang; Yanan Liu; Mengdi Wang; Qiuli Chao; Liying Wang; Danna Li; Huaying Fan; Daquan Chen; Linyu Li; et al. (Journal of Natural Medicines, 2019)

Identification of β-carboline and canthinone alkaloids as anti-inflammatory agents but with different inhibitory profile on the expression of iNOS and COX-2 in lipopolysaccharide-activated RAW 264.7 macrophages - Pan Liu; Huixiang Li; Ruiling Luan; Guiyan Huang; Yanan Liu; Mengdi Wang; Qiuli Chao; Liying Wang; Danna Li; Huaying Fan; Daquan Chen; Linyu Li; et al. (Journal of Natural Medicines, 2019)

bFGF and Activin A function to promote survival and proliferation of single iPS cells in conditioned half-exchange mTeSR1 medium - Xiaoling Guo; Ruiling Lian; Yonglong Guo; Qing Liu; Qingshan Ji; Jiansu Chen (Human Cell, 2015)

Differential Immune Responses and Protective Effects in Avirulent Mycobacterial Strains Vaccinated BALB/c Mice - Laicheng Liu; Ruiling Fu; Xuefeng Yuan; Chunwei Shi; Shuling Wang; Xianyu Lu; Zhao Ma; Xiaoming Zhang; Weiyan Qin; Xionglin Fan (Current Microbiology, 2015)

Zacopride selectively activates the Kir2.1 channel via a PKA signaling pathway in rat cardiomyocytes - Li Zhang; QingHua Liu; ChengFang Liu; XuWen Zhai; QiLong Feng; RuiLing Xu; XiangLi Cui; ZhiQing Zhao; JiMin Cao; BoWei Wu (Science China Life Sciences, 2013)